Dinamika Mualaf dalam Proses Asimilasi di Lingkungan Minoritas Muslim di Denpasar Bali (Komunitas Mualaf di Genta Mualaf Indonesia) - Fredyarini, Novena Ade; Kusjuniati, Kusjuniati (Proceedings of Annual Conference for Muslim Scholars, 2022)
Mualaf is someone who converts religion and needs guidance and guidance about Islam in the role of kaffah. In the holistic aspect, Denpasar residents with a Hindu majority make limited space for movement and activities for Muslim citizens. During the pandemic, the existence of Mualaf community was seen in one of the Muallaf in Denpasar, namely GMI (Genta Mualaf Indonesia). Based on the process of activities carried out by GMI in Denpasar, it can be formulated in the focus of the research, namely, how are the dynamics of Mualaf in the process of assimilation in the Muslim minority environment? The aim of knowledge and explain the process of assimilation of Mualaf to Islam at GMI Denpasar. This research uses qualitative research methods with descriptive qualitative and interpretive research types. The data collection technique was purposive sampling, namely members of the Denpasar GMI community. Through this research, it is possible that it can provide references and contributions to communities and other areas during the pandemic. As an effort to embrace and foster Mualaf to remain in existence in live a new life through religious moderation.